Agroforestry Drives Root Plasticity and Increases Water Productivity for Roots in North China - Huasen Xu, Xin Pan, Shuangshuang Liu, Weiming Wang, Zhimei Sun (Forest Chemicals Review, 1970)
In tree-based agroforestry systems, plant would express trait plasticity to adapt the highly environmental heterogeneity and vary resource acquisition strategies. This poses a challenge for revealing the underlying relation between roots and soil water in agroforestry. Fieldwork was conducted in a 5 year old apple (Malus pumila) orchard in North China, including the apple-soybean (Glycine max) agroforestry, apple monoculture and sole soybean, to determine root distribution and water utilization. Root biomass density of apple and soybean were lower than those of monocultures, with averagely decrease of 39.7 g m-3 for apple and 185.0 g m-3 for soybean. The intercrop row adjacent to the tree row showed lower root biomass density than intercrop rows further away from the tree row, but apple trees represented an opposing distribution. Mean rooting depth of different components in agroforestry also showed an opposite growth trend in vertical soil profile. Introducing soybean into apple orchard obviously affected soil water compared to the sole stand, but water productivity for roots in agroforestry was higher than that in monocultures. Water equivalent ratio for root production was 1.33 when the partial water equivalent ratios were declined significantly 0.13 of soybean and slightly 0.04 of apple in agroforestry. The root biomass density expressed a significantly negative influence on soil moisture in the apple-soybean agroforestry and apple monoculture. In general, the competition and complementarity between apple and soybean with strong root plasticity can promote water utilization of root production in agroforestry.